2019
DOI: 10.12688/f1000research.19174.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding context-dependent mechanisms controlling neurotrophin signaling and function

Abstract: Complex mechanisms control the signaling of neurotrophins through p75NTR and Trk receptors, allowing cellular responses that are highly context dependent, particularly in the nervous system and particularly with regard to the neurotrophin brain-derived neurotrophic factor (BDNF). Recent reports describe a variety of sophisticated regulatory mechanisms that contribute to such functional flexibility. Mechanisms described include regulation of trafficking of alternative BDNF transcripts, regulation of post-transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 58 publications
2
23
0
1
Order By: Relevance
“…Similar outcomes of the enhanced neurotrophic potential of hADSC in response to HPL-conditioning were reported recently in a co-culture in vitro model with chicken embryonic DRG [51]. Whether such factors could be internalized by cells during culture [52] and potentially released or influencing hADSC gene/protein expression will be a matter of further in vitro studies of our group, together with in vivo applications.…”
Section: Discussionsupporting
confidence: 78%
“…Similar outcomes of the enhanced neurotrophic potential of hADSC in response to HPL-conditioning were reported recently in a co-culture in vitro model with chicken embryonic DRG [51]. Whether such factors could be internalized by cells during culture [52] and potentially released or influencing hADSC gene/protein expression will be a matter of further in vitro studies of our group, together with in vivo applications.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, the evolutionarily-conserved molecular mechanisms we investigated in the context of synaptogenesis, such as TrkB and sensorin signaling, MAPK activation, and CREB-dependent transcription, are known to be engaged during learning-related synaptic plasticity in the same and other systems 3,4,25,26,32,34,35,39 . While clear similarities between the two programs of plasticity have been previously described [7][8][9][10] and were suggested by our present findings (e.g., activation of MAPK and of TrkB and sensorin signaling), our results also revealed differences in the valence of transcriptional effects (e.g., C/EBP downregulation vs. upregulation in learning). Taken together with previous research in Aplysia, the present study reveals novel molecular mechanisms of plasticity that could represent points of contact between developmental synapse formation and experience-dependent synaptic restructuring.…”
Section: Discussionsupporting
confidence: 82%
“…BDNF, one of the mammalian TrkB ligand orthologs, has been shown to act in an autocrine manner to stabilize cyclic AMP-dependent axon initiation and growth 28 . Interestingly, BDNF can act through TrkB receptors to promote neural development and synaptic strengthening, and through the p75NTR receptor to promote neuronal death and synaptic depression 10 . Moreover, reports from the mammalian and invertebrate literature have shown that the same growth factor can both promote and inhibit synaptogenesis by signaling through distinct receptors and inducing different downstream signaling [44][45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophin signaling plays an essential role in maintaining neuronal survival and synaptic plasticity as well as learning and memory (Bothwell, 2019). BDNF is predominant among the several neurotrophins in the adult central nervous system.…”
Section: Cell Survival System: the Trkb Signaling Pathwaymentioning
confidence: 99%
“…This mechanism protects neurons from oxidative damage during excitotoxic stimulation with glutamate, an event that frequently encountered in neural injury, stroke, and NDDs ( Ishii and Mann, 2018 ). Moreover, BDNF-TrkB.T1-p75 NTR -Nrf2-mediated neuroprotection is context-dependent ( Bothwell, 2019 ), i.e., it depends on the degree of activation. However, there is no evidence, so far, demonstrating the association of the neuroprotective phytochemicals with this signaling pathway suggesting further investigation.…”
Section: Cross-talk Between Trkb Signaling Pathway and Nrf2-are Antiomentioning
confidence: 99%